The Completion Pattern of Adultery Case Based on the Customary Law of Sabunese - Paulus, Gery Mario; Pello, Jimmy; Sinurat, Aksi (JILS (Journal of Indonesian Legal Studies), 2019)
Adultery, according to Sabu Society is relations between a man who is bound a custom matrimony or religious marriage with a woman who is bound a matrimony or one of them has bound in a matrimony. Adultery, based on the positive law is ruled in chapter 284 book of Undang-Undang Hukum Pidana (KUHP). Chapter 284 KUHP has the point that a man or woman who has been married and doing adultery (overspel). The point in chapter 284 KUHP has similarity with the point in customary law of Sabunese, namely adultery is conducted with someone (man or woman) who has been joined in matrimony. Based on the research has been done, it found that the people of Sabu is prefer to completing adultery customarily because of some factors, that is: sanction and serious fine, it is normally using the completion customarily with the people of Sabu,the justice law based on the people of Sabu, the effect of completion and completion pattern. Two patterns of completion which appears in completion process of adultery based on the customary law of Sabu is the completion pattern in kinship way which are preventing and protecting.